Finite elemental assessment of torsional behavior of RC beams having different shear reinforcement - Juhin, Warda Jannat; Ahmed, Raihan Uddin; Mahzuz, H. M. A.; Islam, Md. Ariful (Building Engineering, 2024)
In this paper, the torsional behavior of 8 beams in 4 categories with 2 different ultimate concrete compressive strengths (22.92 MPa and 43.47 MPa) was evaluated, and the best alternative of shear reinforcement pattern compared to the conventional non-welded rectangular stirrup beam (NRSB) was determined. 4 types of beams were modeled using SolidWorks, namely—Non-welded Rectangular Stirrup Beam (NRSB), Welded Rectangular Stirrup Beam (WRSB), Normal Welded Warren Truss-shaped Beam (NWWTB), and Flipped Welded Warren Truss-shaped Beam (FWWTB). The dimension and weight of reinforcement were kept the same for all beams. After simulating using ANSYS, it was seen that WRSB specimens had the largest torsional moment capacity, while NWWTB in normal orientation showed marginal improvement compared to NRSB.